Variae Lectiones (Qirā’āt) Dalam Perspektif Gabriel Said Reynolds: (Studi Pemikiran Orientalis) - Fauzi, Ahmad (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
This paper examines Gabriel Said Reynolds’s view of the variety of reading in the Quran, both canonical and non-canonical qiraah, authenticity and its function in the Quranic intrepretation. The majority of Muslim Scholars believe that qiraat in Ottoman Manuscripts are mutawatir and sourced from the Prophet Muhammad saw, while the other qiraat than qiraat contained in Ibn Masud’s Manuscripts, Ubay bin Kaab’s Manuscripts are considered qiraah syazah and are not recognized by Muslim authorities because the chain of sanad is considered problematic. But Gabriel Said Reynolds’s opinion says that the existence of a variety of readings in Ottoman Manuscripts is due to reading speculations carriead out by ancient quran readers due to the absence of dots and diacritical marks in the available texts, making the reader free to sound the word according to his wishes. Reynolds also claimed many qiraat outside the Ottoman Manuscripts which were used by the commentators as justification for his interpretation. Through this study, the authors concluded that Gabriel Said Reynolds doubted the authenticity of qiraat in Ottoman Manuscripts. Reynolds’s view is interesting to study, because it contradicts the general view of Muslim scholars who consider that the existing qiraat is a variety of quran reading which is believed to be sourced directly from the Prophet Muhammad saw.